PENGARUH BAURAN PEMASARAN SYARIAH TERHADAP KEPUTUSAN PEMBELIAN PRODUK HAMMAYIM PADA PELANGGAN TOKO AL-ZAYTUN - Almi Maliana Juwita; Sobirin; Muhammad Nur Kholish Abdurrazaq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of the Islamic marketing mix, which includes product (X1), price (X2), distribution (X3), promotion (X4), people (X5), process (X6), and performance (X7), on the purchase decision (Y) of Hammayim bottled water among customers of Toko Al-Zaytun. A quantitative approach was chosen to examine the relationships between variables, using a survey method involving 80 respondents as the sample. Primary data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity), ANOVA, multiple linear regression analysis, and coefficient of determination. The results indicate that the variables of product, price, promotion, people, and performance have a positive and significant effect. In contrast, the process variable has a negative and significant effect, while the distribution variable shows no significant influence. The coefficient of determination reveals that 87.3% of purchase decisions are influenced by the Islamic marketing mix variables studied, while the remaining 12.7% are affected by other factors outside the research model. These findings demonstrate that the Islamic marketing mix plays a dominant role in shaping consumer purchase decisions for bottled drinking water products. Keywords: Islamic Marketing Mix, Purchase Decisions, Bottled Drinking Water Products;